Prevalence of Gastro-Intestinal Parasitic Infestation in Cows with Various Reproductive Ailments in Tribal Areas of Himachal Pradesh - Sharma, Ankita; Singh, Madhumeet; Kumar, Pravesh (The Indian Journal of Animal Reproduction, 2024)
Gastrointestinal (GI) parasitic infection poses a significant concern in cattle management. The influence of gastrointestinal  (GI) parasites on reproduction is contingent on multiple factors. Faecal samples were collected from 285 reproductively  compromised, normal cyclic and pregnant cattle from five different tribal zones of Himachal Pradesh viz. Lahaul, Spiti,  Kinnaur, Pangi and Bharmour. Coprological examination revealed the presence of gastro-intestinal parasites in 47 percent  of cattle whereas 52.9 percent cattle were bereft of it. Incidence of gastro-intestinal parasites was highest (15.7%) in  true anestrus cows followed by endometritis (12.2%), pregnant cattle (9.4%), silent estrus (6.3%), miscellaneous (2.1%),  and normal cyclic (1.05%), respectively. Overall incidence of different parasites i.e., strongyles, oocyst of protozoans  (Coccidia), amphistomes, cestodes (Moneizia spp.) and mixed infestation was 25.61, 5.61, 2.45, 0.3 and 12.98 percent,  respectively. Among the different physiological and pathological conditions, anestrus cows had the highest incidence  (22%) for parasitic load.
Keywords: Gastro-intestinal parasites; Tribal; Cattle; Anestrus; Incidence